Effect of Exercise Preconditioning on Myocardia Ischemia-Reperfusion Injury in Aged Rats - Hongyu LI; Xia YIN; Shiqiang ZHANG; Luwen ZHU; Qiang TANG (康复学报)
Objective:To observe the effects of exercise preconditioning on cardiac function, myocardial infarct area, cardiomyocyte ultrastructure and antioxidant capacity of aged rats after isolated myocardial ischemia-reperfusion injury.Methods:A total of 60 SPF male SD aged rats were randomly divided into the control group (Con group), the ischemia-reperfusion model group (IR group), the exercise preconditioning+ischemia-reperfusion group (EP+IR group), the ischemic preconditioning group (IPC group) and the exercise preconditioning+ischemic preconditioning group (EP+IPC group), with 12 rats in each group. The Con group, IR group and IPC group received no special exercise intervention, while the EP+IR group and the EP+IPC group received exercise preconditioning intervention (using electric animal experimental treadmill for gradient exercise training, once a day, five days a week, continuous training for six weeks). The isolated myocardial ischemia-reperfusion model of aged rats was made by using Langendorff device. The details were as follows: the Con group only received isolated myocardial perfusion, continuous balance perfusion for 180 minutes without ischemia operation; the IR group balanced preperfusion for 20 minutes, and then kept the heart temperature constant at 37℃, the whole heart was subjected for 40 minutes by controlling the three-way valve of the perfusion equipment, and then reperfusion for 120 minutes; After rats'heart were separated, the model preparation method of the EP+IR group was the same as the IR group; After balance perfusion for 20 minutes in vitro, the hearts of rats in the IPC group received ischemia preconditioning for three times (transient ischemia for 5 minutes, followed by reperfusion for 10 minutes), followed by ischemia for 40 minutes, and then was reperfused for 120 minutes; the model preparation method of the EP+IPC group was the same as the IPC group. The changes of cardiac function were recorded by multi-channel physiological recorder before reperfusion and after reperfusion for 30, 60 and 120 minutes; the TTC staining was used to determine infarct area, the colorimetry was used to determine the activity of LDH in coronary effluent, MDA content and SOD activity in myocardial tissue.Results:①Indexes of cardiac function: compared with the Con group at the same time, the indexes of cardiac function[heart rate (HR), left ventricular developed pressure (LVDP), ±dp/dtmax, coronary flow (CF) ]decreased significantly in the IR group before reperfusion and after reperfusion for 30, 60 and 120 min. Compared with the IR group at the same time, the indexes of cardiac function in the EP+IR, IPC and EP+IPC group increased significantly after reperfusion for 30, 60 and 120 min (P< 0.05). Compared with the IPC group at the same time, the indexes of cardiac function (such as HR, LVDP, ±dp/dtmax, CF) after reperfusion for 30, 60 and 120 min in the EP+IPC group were significantly higher (P< 0.05). ②Myocardial infarct area: compared with the Con group, the myocardial infarct area in the IR group increased significantly (P< 0.05); compared with the IR group, the myocardial infarct area in the EP+IR, IPC and EP+IPC group decreased significantly (P< 0.05). ③LDH activity, MDA content and SOD activity: compared with the Con group, LDH activity in the IR group was significantly higher (P< 0.05); compared with the IR group, LDH activity in EP+IR, IPC and EP+IPC group was lower (P< 0.05); compared with the EP+IR, IPC group, the LDH activity in the EP+IPC group was significantly lower (P< 0.05). Compared with the Con group, MDA content of the IR group increased significantly and SOD activity of the IR group decreased significantly (P< 0.05); compared with the EP+IR, IPC group, MDA content of the EP+IPC group was significantly lower and SOD activity of the EP+IPC group was significantly higher (P< 0.05).Conclusion:Exercise preconditioning can induce the protective effect of IPC in aged myocardium, improve effectively the cardiac function of aged rats with myocardial ischemia-reperfusion injury, reduce the area of myocardial infarction and alleviate cardiomyocyte injury, which may be related to the decrease of myocardial LDH activity and MDA content, the increase of SOD activity and the enhancement of myocardial antioxidant capacity during myocardial ischemia-reperfusion.